Six months survival and risk factors for attrition for patients detected with cryptococcal antigenemia through screening in Malawi. - Master R O Chisale; Alex Jordan; Pocha S Kamudumuli; Bernard Mvula; Michael Odo; Alice Maida; James Kandulu; Ben Chilima; Frank W Sinyiza; Pauline Katundu; Hsin-Yi Lee; Rebecca Mtegha; et al. (PLoS ONE, 2023)
Main objective A cohort of adult Malawian people living with HIV (PLHIV) testing positive for cryptococcal antigenemia was observed and followed to determine the outcomes and risk factors for attrition. Methods concept Eligible PLHIV were enrolled at 5 health facilities in Malawi, representing different levels of health care. ART naïve patients, ART defaulters returning to care, and patients with suspected or confirmed ART treatment failure with CD4 <200 cells/μL or clinical stage 3 or 4 were enrolled and received CrAg tests on whole blood specimens from August 2018 to August 2019. Hospitalized PLHIV were enrolled and tested for CrAg from January 2019 to August 2019, regardless of CD4 or clinical stage. Patients with cryptococcal antigenemia were managed per Malawian clinical guidelines and were followed up for six months. Survival and risk factors for attrition at six months were assessed. Results A total of 2146 patients were screened and 112 (5.2%) had cryptococcal antigenemia. Prevalence ranged from 3.8% (Mzuzu Central Hospital) to 25.8% (Jenda Rural Hospital). Of the 112 patients with antigenemia, 33 (29.5%) were diagnosed with concurrent CM at the time of enrollment. Six-month crude survival of all patients with antigenemia (regardless of CM status) ranged from 52.3% (assuming lost-to-follow-up (LTFU) patients died) to 64.9% (if LTFU survived). Patients who were diagnosed with concurrent CM by CSF test had poor survival (27.3-39.4%). Patients with antigenemia who were not diagnosed with concurrent CM had 71.4% (if LTFU died)- 89.8% (if LTFU survived) survival at six months. In adjusted analyses, patients with cryptococcal antigenemia detected after admission to inpatient care (aHR: 2.56, 1.07-6.15) and patients with concurrent CM at the time of positive antigenemia result (aHR: 2.48, 1.04-5.92) had significantly higher hazard of attrition at six months. Conclusions Overall, our findings indicate a need for routine access to CrAg screening and pre-emptive fluconazole treatment as a way to detect cryptococcal antigenemia and prevent CM in outpatient and inpatient settings. Rapid access to diagnosis and treatment for cryptococcal meningitis (CM) with gold-standard antifungals is needed to improve survival of patients with advanced HIV in Malawi.